2007
DOI: 10.1097/jsm.0b013e31802b4fda
|View full text |Cite
|
Sign up to set email alerts
|

Low-Intensity Exercise Improves Quality of Life in Patients With Crohn's Disease

Abstract: These inconsistencies highlight the need for greater awareness and standardization of diagnostic criteria. This work may serve as the foundation for more universal treatment plans and subsequently more meaningful clinical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
106
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(108 citation statements)
references
References 13 publications
1
106
0
1
Order By: Relevance
“…In a mouse model of colitis, forced exercise resulted in an increased mortality rate, whereas voluntary training had a protective effect on inflammation and diarrhea [39]. Regarding the relationship between exercise and course of disease in humans, our results suggest that moderate PA is feasible in stable IBD patients with mild activity, which is in accordance with data collected from previous clinical trials [29,30,31,38,40]. Randomized controlled trials with adequate statistical power may be able to build on the current trial and definitively illustrate the effects of different volumes and intensities of PA on HRQOL and symptoms in IBD.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In a mouse model of colitis, forced exercise resulted in an increased mortality rate, whereas voluntary training had a protective effect on inflammation and diarrhea [39]. Regarding the relationship between exercise and course of disease in humans, our results suggest that moderate PA is feasible in stable IBD patients with mild activity, which is in accordance with data collected from previous clinical trials [29,30,31,38,40]. Randomized controlled trials with adequate statistical power may be able to build on the current trial and definitively illustrate the effects of different volumes and intensities of PA on HRQOL and symptoms in IBD.…”
Section: Discussionsupporting
confidence: 81%
“…No adverse events were observed, and the patients improved HRQOL measured by total IBDQ scores [29]. Ng and colleagues also investigated the effect of a three-month low-intensity walking program (30 min of walking, thrice a week) in CD patients with moderate disease, and although improvements in HRQOL were observed, there were no differences between groups [30]. In another study, 16 patients suffering from ulcerative colitis (UC) participated in six hours per week of stress management training, moderate physical exercise, and behavioral techniques for a total of 10 weeks [31].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, none of these systems has undergone reliability testing or validation. It is not surprising that there is no standard method to classify instability and that studies have demonstrated that patients may be given different diagnoses when different methods of classifying instability are used,5 and that physicians have poor agreement in how they describe the same patient 7…”
Section: Classification Of Instabilitymentioning
confidence: 99%
“…This confusion has been highlighted by McFarland et al ,5 who compared four different classification systems for patients with instability and found great variation, particularly with regard to multidirectional instability, leading the editors of the Journal of Bone and Joint Surgery to opine that the article by McFarland et al 5 was a “…provocative call to action”, and “Until the criteria for diagnosis are clearly defined, investigators will be unable to contribute in a compelling way to understand the condition since they cannot know whether studies are comparing ‘apples and oranges'.”6 This confusion in how instability is defined was also demonstrated by Chahal et al ,7 who found that physicians had poor agreement when asked to classify clinical scenarios of glenohumeral joint instability. These works provide evidence that we need better ways of defining and classifying glenohumeral joint instability.…”
mentioning
confidence: 93%
“…However, the evidence for exercise in Crohn’s disease is sparse, with only a handful of small prospective trials [1, 2], with methodological limitations, including the use of non-randomised and non-controlled study designs and small sample sizes. Here, we describe the protocol for a study that aims to assess the feasibility and acceptability of two common types of exercise training—high-intensity interval training (HIIT) and moderate-intensity continuous training (MICT)—in adults with inactive or mildly active Crohn’s disease (CD).…”
mentioning
confidence: 99%